INTEGRÁCIA HROMADNEJ OSOBNEJ DOPRAVY V PODMIENKACH SLOVENSKEJ REPUBLIKY (Perner's Contacts, 2007)
The aim of this article is integration of passenger mass transport in Slovak Republic. The article analyses the present status of legal modifications of passenger mass transport and public interests in transport too. It solve initial sequence of steps for removal limitations in legislative and describe Public mass transport law as top possible legislative integration tool of transport services.
Keywords: integrated transport system; passenger mass transport; legislation